Le corps de l’écrivain, instrument et enjeu de reconnaissance - Paul Dirkx (Carnets)
This study formulates a set of assumptions concerning the relations between literary recognition and the bodies of the writers. In a first part, a differential approach allows to make a clear distinction between the concepts of recognition, notoriety, legitimacy, legitimation, consecration, canonisation, classicisation and ‘panthéonisation’. After this necessary clarification, it will be possible to look at what seems to be the foundation of literary recognition mechanisms: literary autonomy, based on a specifically literary form of belief. This will lead to introduce the concept of incorporation and to consider writers in both their somatic and symbolic dimensions, which are inseparably linked. Finally, some assumptions will be qualified through two examples of writers who have been putting into their texts their own writer’s body: Claude Simon and Christian Dotremont.